Collaborative Online Writing: Students’ Perspectives and Their Actual Writing Performance - Syamdianita Syamdianita; Gita Mutiara Hati (Script Journal: Journal of Linguistics and English Teaching, 2025)
Background: This study explores a topic that has not received enough attention in the literature: the relationship between EFL students' perceptions of online collaborative writing and their actual writing performance. Few studies have specifically looked at how learners' self-assessments match quantifiable writing outcomes, despite prior research emphasizing the advantages of collaborative writing for language development. Methodology: 91 Indonesian EFL undergraduate students took part in this study by working together to write an argumentative essay while receiving online instruction. Open-ended surveys, self-perception questionnaires, documentation of online collaborative interactions, and student essays were used to gather data. Findings: According to both quantitative and qualitative analyses, the majority of students had favorable opinions about collaborative writing and thought it improved their speaking and writing confidence. Statistical analysis, however, revealed no meaningful relationship between students' assessments of themselves and their actual writing abilities. Conclusion: These results underline the need for more reflective and feedback-rich writing instruction in EFL contexts by indicating that students may misjudge their own writing abilities. Originality: The originality of this study lies in its dual focus on EFL students' self-perceptions and their actual writing performance within an online collaborative writing context. Unlike previous research that typically examines these aspects separately, this study uniquely correlates self-assessment with quantifiable writing outcomes, particularly in the demanding genre of argumentative writing. Conducted in an Indonesian EFL setting during remote learning, it highlights important cultural and technological influences often overlooked in similar studies. Thus, it provides a novel perspective on the gap between students' perceived and actual writing abilities in online collaborative environments.